Post harvest physical and mechanical properties of Baccaurea motleyana fruits / Nafisah Bustaman, Mohd Haris Ridzuan Ooi Abdullah and Ch'ng Pei Eng - Bustaman, Nafisah; Abdullah, Mohd Haris Ridzuan Ooi; Ch'ng, Pei Eng (2020)
Some post harvest physical and mechanical properties of Baccaurea motleyana fruits were determined in order to facilitate the design of machines or equipments to handle, process and store the fruits. They consist of the mean moisture content, length, width, thickness, geometric mean diameter, mass, volume, surface area, sphericity, aspect ratio, true density, bulk density, porosity and coefficient of static friction on different types of surface. The physical and mechanical properties were determined at the moisture content (wet basis) of 80.79 ( 1.49) %. The mass, volume and dimensions of Baccaurea motleyana fruits were measured by using electronic balance, water displacement method and vernier caliper respectively. The geometric mean diameter, surface area, sphericity, aspect ratio, true density, bulk density and porosity were calculated using different theoretical equations. The mean length, width and thickness of the fruits were 24.69 ( 1.49), 22.49 ( 1.65) and 20.35 ( 2.15) mm, respectively. The average value of geometric mean diameter, mass, volume, surface area, sphericity, aspect ratio, true density, bulk density and porosity were 22.43 ( 1.69) mm, 5.885 ( 1.236) g, 6146.67 ( 1505.64) mm3, 1589.16 ( 238.85) mm2, 90.77 ( 2.46) %, 91.04 ( 3.57) %, 1039.70 ( 125.24) kgm-3, 484.71 ( 24.95) kgm-3 and 97.48 ( 0.61) %, respectively. The mean value of coefficient of static friction on four types of structural surface were found to be varying from 0.158 ( 0.028) for galvanized steel sheet to 0.209 ( 0.034) for rubber surface.